2008
DOI: 10.2478/s11686-008-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Some philometrid nematodes (Philometridae), including four new species of Philometra, from marine fishes off New Caledonia

Abstract: Examinations of marine fishes off New Caledonia, South Pacific, carried out in [2003][2004][2005][2006], yielded some nematodes of the genus Philometra Costa, 1845, including the following three new species: P. cyanopodi sp. nov. (males and subgravid females) and P. lethrini sp. nov. (males and subgravid females) from the gonads of Epinephelus cyanopodus (Richardson) (Serranidae) and Lethrinus genivittatus Valenciennes (Lethrinidae), respectively, and P. lagocephali sp. nov. (gravid female) from the abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
0
31
0
2
Order By: Relevance
“…Based on the total body length of females alone, the worms from the current study (25 -43 . In this regard, the current female philometrids were morphologically confirmed to be P. thaiensis based on their morphological similarities with the reported gravid female of that species (Moravec et al, 2004(Moravec et al, , 2012Moravec & Justine, 2008). Although the males were not found from the host fishes by Moravec et al (2004), the identity of the site of infection (abdominal cavity), the same country of origin (Thailand), aquatic environment (freshwater), and the genus of the host fish (Tetraodon), in addition to the considerable morphological similarity of P. thaiensis described (Moravec et al, 2004), indicate that the species of Philometra males from the eyespot pufferfish is P. thaiensis.…”
Section: Commentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on the total body length of females alone, the worms from the current study (25 -43 . In this regard, the current female philometrids were morphologically confirmed to be P. thaiensis based on their morphological similarities with the reported gravid female of that species (Moravec et al, 2004(Moravec et al, , 2012Moravec & Justine, 2008). Although the males were not found from the host fishes by Moravec et al (2004), the identity of the site of infection (abdominal cavity), the same country of origin (Thailand), aquatic environment (freshwater), and the genus of the host fish (Tetraodon), in addition to the considerable morphological similarity of P. thaiensis described (Moravec et al, 2004), indicate that the species of Philometra males from the eyespot pufferfish is P. thaiensis.…”
Section: Commentsmentioning
confidence: 92%
“…There is a high degree of host specificity among philometrid species, wherein species are characterized morphologically, including their location in the host (Moravec, 2006 Except for P. balistii, which infects the oculo-orbits of its fish hosts, these Philometra species were located in the abdominal cavity of their host fishes, all belonging to the family Tetraodontidae (Moravec, 2006;Moravec et al, 1992;Moravec et al, 2004;Moravec & Justine, 2008;Moravec et al, 2012). In the current study, another freshwater ornamental fish, the eyespot pufferfish from Thailand, was found to be infected with nematodes belonging to the genus Philometra.…”
Section: Commentsmentioning
confidence: 99%
“…Moravec and Justine (2008) also reported one subgravid and one nongravid female of Philometra sp. from the ovary of the only specimen of Lutjanus vitta (Quoy et Gaimard) (Lutjanidae) examined from New Caledonian waters in October of 2006.…”
mentioning
confidence: 99%
“…To date, the following five gonad-infecting species of Philometra have been recorded from marine fishes of the families Lethrinidae, Priacanthidae, Serranidae and Tetraodontidae from the South Pacific Ocean off the coast of New Caledonia: Philometra cyanopodi Moravec et Justine, 2008, P. fasciati Moravec et Justine, 2008, P. lethrini Moravec et Justine, 2008, P. priacanthi Moravec et Justine, 2009 and P. tenuicauda Moravec et Justine, 2009) (see Moravec and Justine 2005, 2008). Moravec and Justine (2008) also reported one subgravid and one nongravid female of Philometra sp.…”
mentioning
confidence: 99%
“…Among these, males have been described in only a few species. In contrast, the majority of species were classified based on observation of semigravid and/or gravid females (Merella et al 2005;Moravec 2006;Moravec and Salgado-Maldonado 2007;Moravec et al 2008a, b;2010a, b;2011a, b;Moravec and Justine 2008Quiazon et al 2008a, b;Gaglio et al 2009;de Buron 2009, 2013). In all likelihood, a number of philometrid nematodes have yet to be discovered and identified in Philippine waters.…”
Section: Discussionmentioning
confidence: 99%